Respuesta :
Step-by-step explanation:
Let's solve your equation step-by-step.
−9m2−8m−3=0
For this equation: a=-9, b=-8, c=-3
−9m2+−8m+−3=0
Step 1: Use quadratic formula with a=-9, b=-8, c=-3.
m=
−b±√b2−4ac
2a
m=
−(−8)±√(−8)2−4(−9)(−3)
2(−9)
m=
8±√−44
−18
Answer:
No real solutions.
The given equation has no real solutions.
We have given that the quadratic equation
[tex]-9m^2-8m-3=0[/tex]
For this equation: a=-9, b=-8, c=-3
[tex]-9m^2-8m-3=0[/tex]
Step 1: Use quadratic formula with a=-9, b=-8, c=-3.
What is the formula for the quadratic roots?
[tex]x=\frac{-b \±\sqrt{b^2-4ac}} {2a}[/tex]
Therefore we have,
[tex]x=\frac{-b \±\sqrt{b^2-4ac}} {2a}[/tex]
[tex]x=\frac{-(-8)\±\sqrt{(-8)^2-4(-9)(-3)} }{2(-9)}[/tex]
[tex]x=-\frac{4}{9} -i\frac{\sqrt{11} }{9}[/tex] and [tex]x=-4/9+i\frac{\sqrt{11} }{9}[/tex]
This equation has no real solutions.
To learn more about the quadratic equation visit:
https://brainly.com/question/1214333